Hyaluronic acid-modified didecyldimethylammonium bromide/ d-a-tocopheryl polyethylene glycol succinate mixed micelles for delivery of baohuoside I against non-small cell lung cancer: in vitro and in vivo evaluation - Hongmei Yan; Jie Song; Xiaobin Jia; Zhenhai Zhang (Taylor & Francis Group, 2017)
Baohuoside I is an effective but a poorly soluble antitumor drug. In this study, we prepared baohuoside I-loaded mixed micelles with didecyldimethylammonium bromide (DDAB) and d-a-tocopheryl polyethylene glycol succinate (TPGS) (DTBM) and active targeting mixed micelles (HDTBM) with hyaluronic acid (HA) as the targeting ligand on the surface of the mixed micelles. We performed a systematic comparative evaluation of the antiproliferative effect, cellular uptake, antitumor efficacy, and in vivo tumor targeting of these micelles using A549 cells. HDTBM showed improved cellular uptake and had a greater hypersensitizing effect on A549 cell lines than baohuoside I; half-maximal inhibitory concentration (IC50) was 8.86 versus 20.42 μg/mL, respectively. Results of the antitumor efficacy study and the imaging study for in vivo targeting showed that the mixed-micelle formulation had higher antitumor efficacy and achieved effective and targeted drug delivery. Therefore, our results indicate that HA/baohuoside I-M may be used as a potential antitumor formulation.